Implementasi Pasal 41 Perda Kota Medan No. 9 Tahun 2016 tentang Penyelenggaraan Lalu Lintas dan Angkutan Jalan terhadap Kelaikan Jalan Bus Kota di Kota Medan Perspektif Siyāsah Dustūriyyah - Anggraini, Esty Dewi; Batubara, Putri Eka Ramadhani (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
This study aims to analyze the implementation of Article 41 of the Regional Regulation of Medan City Number 9 of 2016 concerning the Administration of Road Traffic and Transportation on the roadworthiness of city buses in Medan City, and to examine it from the perspective of siyāsah dustūriyyah. This research employs an empirical legal research method with a qualitative approach, conducted through interviews with the Medan City Transportation Agency, field observations, and the study of laws and regulations as well as fiqh al-siyāsah literature. The results of the study indicate that normatively, Article 41 has regulated the obligation to fulfill technical requirements and the roadworthiness of city buses through periodic KIR testing every six months. However, empirically, its implementation has not been optimal, as evidenced by the continued operation of city buses that are not roadworthy and a decrease in the number of buses passing the KIR test. These conditions are influenced by limited supervision, low compliance among transportation business operators, and a lack of socialization. From the perspective of siyāsah dustūriyyah, the policy on the roadworthiness of city buses constitutes part of the constitutional responsibility of local governments in realizing public welfare (maṣlaḥah ‘ammah), particularly the protection of life (ḥifẓ al-nafs). The suboptimal implementation reflects the failure to fully uphold the mandate of authority in accordance with the principles of justice, benefit, and public safety protection within Islamic constitutional law. This study emphasizes the need to optimize supervision, law enforcement, and legal awareness in order to achieve a safe, orderly, and equitable public transportation system in Medan City.